Coding Climate Crisis Conundrum: Cosmetic Count & Colonial Conspiracy than Compounded Commitment - Dahal, Atindra (Samsad Journal संसद जर्नल, 2025)
Climate discourse- despite being rendered as an issue of global concern- has been mere a cosmetic count than compounded commitment, thus deserves a strong revisit in principle and utmost honesty in practice. Efforts and attempts purported by lead countries are mere formal pretexts to showcase their luxury than fructifying any significant outcomes. World power countries are sucking and siphoning the possible most from the global resources; and, now are alarming the rest with note of climate change discourse and danger. Such a colonial conspiracy-now- ought to be challenged, abjured, condemned and confronted unless they heartily come into proportionate collaboration coupled with commensurate compensation. Based on eight sound logical stand points, ergo, this paper wills to argue that current concern on climate change discourse is mere a cosmetic count and colossal conspiracy from colonial countries than any due and genuine genesis to counter the compelling challenge. It is a soft-power tool in political landscape to extend and elongate their hegemony over other countries of the world.